Dinamika Pembangunan Koalisi Partai Politik Pengusung Calon Tunggal Pemilihan Kepala Daerah Kabupaten Lebak Tahun 2018 - Siti Khodijah; Valina Singka Subekti (Nakhoda: Jurnal Ilmu Pemerintahan, 2020)
This research is related to the coalition that was built by all political parties in presenting a single candidate in the 2018 regional elections. presenting candidates who are ready for the pilkada, this happened in Lebak district, Banten province, for the first time  the Local election  only produced one candidate from the incumbent. This research uses the perspective of  Michael Laver's theory which states that coalitions are formed only to gain political office or are called office-seeking, and is supported by Katz and Mair's theory which states that all parties have the same interests, namely only maintaining their collective survival. This research uses qualitative research methods using case studies. Data were obtained by conducting interviews, collecting documents and studying literature. The results showed that the coalition built by political parties in the Lebak district election had a pragmatic motive, that is all political parties unitedly carry incumbent candidates who ultimately did not provide support to independent candidates so that none became an opposition party. In addition, coalitions are carried out only to maintain power and increase the vote acquisition of political parties ahead of the legislative elections in 2109. However, on the other hand, it shows the failure of political parties to recruit the best cadres of their parties at the local political level. So that the coalition that was built only produced a single candidate without a challenger in the Lebak district election in 2018.